RANCANG BANGUN SISTEM PEMANEN ENERGI ANGIN EXHAUST FAN TURBIN ANGIN SUMBU HORIZONTAL DENGAN PENGARAH ANGIN (WIND TUNNEL) - Reki Aji Saputra; Cokorde Gede Indra Partha; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2021)
Energy consumption in the current era is increasing and only focuses on the use of nonrenewableenergy in this case fossil energy, namely fuel oil which is limited in number and theprice is increasing. One solution is to use alternative energy that can be renewed or renewable,including water energy, solar energy, biomass energy, wind energy and others. Renewableenergy which has been widely used as electrical energy by developed countries is wind energy,in addition to the use of natural wind energy as alternative energy, there is also artificial wind,namely the waste energy from the exhaust fan can be used as a source of energy. analternative energy source option for Wind Power Plant (WPP). The characteristics of the windoutput from the exhaust fan itself spread the wind direction so that the wind energy that can becaptured by the wind turbine is less than optimal, so it is necessary to install a wind tunnel thatis useful for directing or focusing the wind distribution In this study, a wind tunnel has beendesigned which is placed in the direction of the exhaust wind output of the horizontal axis windturbine exhaust fan. With the addition of a wind tunnel, it can increase the wind speed from 3.3m/s to 5.8 m/s or an increase of 76% and power harvesters increase from 0.38 Watt to 0.96Watt or an increase of 153%.